Role of marijuana components on the regenerative ability of stem cells. (21st December 2020) - Miller, Henry; De Leo, Nicholas; Badach, Jeremy; Lin, Andrew; Williamson, John; Bonawitz, Steven; Ostrovsky, Olga
Abstract : Stem cell therapy promotes tissue regeneration and wound healing. Efforts have been made to prime stem cells to enhance their regenerative abilities. Certain marijuana components, namely the non‐psychoactive cannabidiol (CBD) and psychoactive tetrahydrocannabinol (THC), are defined as immunomodulators. 9 We test whether two sources of stem cells, primed with CBD or THC, would demonstrate improved regenerative abilities. Human adipose‐derived stem cells (ASCs) and bone marrow‐derived stem cells (BMDSCs), not obtained from the same individual, were treated with low (300 nM) or high (3 μM) concentration CBD. Porcine ASCs and BMDSCs were isolated from a single pig, and treated with either low or high concentrations of CBD or THC. Transwell migration and MTT proliferation assays were performed on the human ASCs and BMDSCs. Also, transwell migration assay was performed on the porcine ASCs and BMDSCs. Finally, a wound healing scratch assay in porcine primary fibroblasts (PFs) was performed, co‐cultured with the cannabinoid‐treated ASCs. CBD priming at low concentration induces migration by 180% ( P < .01) in porcine ASCs, and by only 93% ( P < .02) in porcine BMDSCs. In porcine stem cells, THC priming at low concentration induces migration by 91.6% ( P < .01) in ASCs but by only 44.3% ( P < .03) in BMDSCs. Compared to PFs co‐cultured with untreated ASCs, PFs co‐cultured with low CBD‐primed ASCs had 75% faster wound closure at 18 hours ( P < .01). CBD and THC priming of ASCs and BMDSCs, particularly at lower doses, enhances a number of regenerative parameters, suggesting that these major marijuana components may improve stem cell‐based therapies. Significance of the study: Our study demonstrates that cannabinoids can enhance the regenerative capacity of two major sources of stem cells, adipose‐ and bone marrow‐derived, from human and porcine donors. Stem cell isolation and expansion is invasive, costly and time consuming. Stem cells with improved regenerative properties may be effective in the treatment of acute or chronic wounds. This is the first study to compare the priming potential of two sources of stem cells from the same animal, with the same genetic and epigenetic profile, as well as the first to prime with THC.